2022
DOI: 10.1021/acsaelm.2c01053
|View full text |Cite
|
Sign up to set email alerts
|

P-Type Ohmic Contact to Monolayer WSe2 Field-Effect Transistors Using High-Electron Affinity Amorphous MoO3

Abstract: Monolayer tungsten diselenide (1L-WSe2) has been widely used for studying emergent physics due to the unique properties of its valence bands. However, electrical transport studies have been impeded by the lack of a reliable method to realize Ohmic hole-conducting contacts to 1L-WSe2 especially at low carrier densities and low temperatures. Here, we report low-temperature p-type Ohmic contact to 1L-WSe2 field-effect transistors at carrier densities (n) below n = 1 × 1012 cm–2 with negligible temperature depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…A charge-trapping hysteresis mechanism is illustrated in Figure a for the WSe 2 /Janus-GeSe 2 device, where voltage pulses are applied to the bottom gate to modulate the working state. Previous reports have demonstrated that the ionization potential and bandgap of few-layer WSe 2 are 4.8–5.2 eV , and 1.2 eV, whereas the electron affinity and wide bandgap of multilayer GeSe 2 are 3.3 and 2.7 eV . The WSe 2 /GeSe 2 vdWH forms a type I band alignment (Figure b).…”
Section: Resultsmentioning
confidence: 83%
“…A charge-trapping hysteresis mechanism is illustrated in Figure a for the WSe 2 /Janus-GeSe 2 device, where voltage pulses are applied to the bottom gate to modulate the working state. Previous reports have demonstrated that the ionization potential and bandgap of few-layer WSe 2 are 4.8–5.2 eV , and 1.2 eV, whereas the electron affinity and wide bandgap of multilayer GeSe 2 are 3.3 and 2.7 eV . The WSe 2 /GeSe 2 vdWH forms a type I band alignment (Figure b).…”
Section: Resultsmentioning
confidence: 83%
“…The electrical properties of the WS 2 -FETs were tested using a probe station. The obtained output and transfer characteristic curves, I d – V d and I d – V g , were nonlinear, indicating that a Schottky contact had been formed by a mismatch in the work function between the WS 2 nanosheet and the metal electrode. The carrier mobility of the WS 2 -FETs is calculated using the carrier mobility equation, as follows: μ FE = L C W V normald I V normalg where L is the device channel length, W is the channel width, C is the capacitance per unit area of the SiO 2 dielectric layer (the capacitance C per unit area of 300 nm SiO 2 is 11.5 nF·cm –2 , and the value of capacitance per unit area is inversely proportional to thickness). V d is the drain voltage, and ∂ I /(∂ V g ) is the value of the slope of the tangent line on the transfer curve.…”
Section: Resultsmentioning
confidence: 99%
“…Additional stabilization of copper filaments likely occurs due to the spatial limitation of ion migration by molybdenum oxide. Moreover, copper near molybdenum oxide is expected to lose electrons, given that the work function from a copper crystal is about ∼4.5 eV, and the Fermi level of MoO 3 is estimated to be as low as −6.9 eV (even for amorphous and nonstoichiometric oxides, the levels are similarly low) with a conductance band slightly above it . Consequently, the filament is encircled by two layers of spatial charge: positive on the copper surface and negative on the adjacent molybdenum oxide.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, copper near molybdenum oxide is expected to lose electrons, given that the work function from a copper crystal is about ∼4.5 eV, and the Fermi level of MoO 3 is estimated to be as low as −6.9 eV (even for amorphous and nonstoichiometric oxides, the levels are similarly low) with a conductance band slightly above it. 57 Consequently, the filament is encircled by two layers of spatial charge: positive on the copper surface and negative on the adjacent molybdenum oxide. A sufficiently strong electric field is generated within this layer, attracting copper ions away from the surface, thereby reducing the activation energy of the surface diffusion.…”
Section: Rs Mechanism Evaluationmentioning
confidence: 99%